The Russian Federation State Program «Socio-Economic Development of the Far East and the Baikal Region» - Pavel Aleksandrovich Minakir (Prostranstvennaâ Èkonomika, 2013)
The article assesses draft versions of two program documents of socio-economic development of the Far East and the Baikal Region which were prepared by the Ministry of Regional Development of the Russian Federation and the Ministry of the Russian Federation for Development of the Far East. It is shown that the above documents are not programs in the classic sense because they don’t include the centralized and precisely targeted mechanisms of project financing, aimed at maximizing systemic effects. The authors find the programs objectives fuzzy and overly broad. As a way of increasing the practical implementability of the program the study suggests simplifying the initial system, ensuring the formalizability of goals and clarifying linkages. This can be done on the basis of the principle of diversity reduction to the minimum required size